D-loop Mitochondrial genetic analysis in Abeerden Angus old type from Argentina - Villegas Castagnasso, Egle Etel (2015)
The massive use of reproductive breeding technologies (mainly Artificial Insemination and Embryo Transfer) resulted in an important decrease in the diversity in many breeds, and some genetic lines have been lost. Within the Angus breed, the “New Type” gain importance since 1970, leaving the “Old Type” to a reduced number of herds in the whole world. The objective of this work was to determine the genetic diversity in an “Old Type” herd in Argentina. DNA samples were analyzed for sequence variation in the hypervariable region of the mitochondrial DNA (D-loop). Sequence comparison and phylogenetic analyses revealed that haplotypes fell into European haplogroup (T3) in general, and in particular had high similarity with British haplotypes. Six distinct haplotypes were obtained, that differed from zero to four DNA bases with respect to the nodal sequence T3, with a nucleotide diversity of 0.442. Matrilineages genetic analysis suggested a Scottish origin of this herd. These results suggest that this herd could be a genetic reservoir of the Old Scottish Aberdeen Angus cattle.